1999
DOI: 10.1375/136905299320565988
|View full text |Cite
|
Sign up to set email alerts
|

A religious upbringing reduces the influence of genetic factors on disinhibition: Evidence for interaction between genotype and environment on personality

Abstract: I nfor mati on on per sonal i ty, on anxi ety and depr essi on and on sever al aspects of r el i gi on w as col l ected i n 1974 Dutch fami l i es consi sti ng of adol escent and young adul t tw i ns and thei r par ents. A nal yses of these data show ed that di ffer ences betw een i ndi vi dual s i n r el i gi ous upbr i ngi ng, i n religious affiliation and in participation in church activities are not influenced by genetic factors. The familial resembl ance for di ffer ent aspects of r el i gi on i s hi gh, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(114 citation statements)
references
References 42 publications
5
107
1
1
Order By: Relevance
“…The SES distribution for this sample is 22.1% of low, 43.8% of middle and 34.1% of high SES (Boomsma et al, 2002). The religious background of the families is comparable to the Dutch population (Boomsma et al, 1999).…”
Section: Participants and Proceduresmentioning
confidence: 63%
“…The SES distribution for this sample is 22.1% of low, 43.8% of middle and 34.1% of high SES (Boomsma et al, 2002). The religious background of the families is comparable to the Dutch population (Boomsma et al, 1999).…”
Section: Participants and Proceduresmentioning
confidence: 63%
“…Evidence for the effect of the genotype × environment interaction on personality comes from a study in Dutch adolescent twins, in which it was shown that a religious upbringing greatly reduces the influence of genetic factors on DISINHIBITION, a trait that closely resembles 'novelty seeking' and that is associated with substance use and abuse 23 .…”
Section: Concordancementioning
confidence: 99%
“…We will concentrate on general demographic (education), lifestyle variables (smoking, alcohol use, physical activity, coffee-and tea-consumption, religious practice) and personality/ mental health (body mass index, burnout, problem behavior, neuroticism). These variables are familial, that is family members resemble each other for those characteristics [11][12][13][14][15][16][17][18]. Therefore, data from nonrespondents will be correlated with the data from the respondents and data from responding family members thus will offer information on the non-respondents.…”
Section: Introductionmentioning
confidence: 99%